Exploration of Absenteeism, Affective Commitment, Organizational Justice, and Job Opportunities as Determinants of Health Care Employee Turnover Intention - Nandita Anisa; Fatmah Bagis; Hengky Widhiandono; Arini Hidayah (Jurnal Ilmu Manajemen, 2026)
High turnover intention in the healthcare sector is a strategic challenge because it can disrupt service continuity and increase the workload of both medical and non-medical personnel. This study aims to analyze the influence of Absenteeism, Affective Organizational Commitment, Organizational Justice, and Alternative Job Opportunities on Turnover Intention in health facility employees by referring to Social Exchange Theory. This study used a quantitative approach through a survey involving a population of 524 employees, with a final sample of 235 respondents working in three hospitals. Data were analyzed using SEM-PLS to examine the relationship between variables. The results showed that Absenteeism and Alternative Job Opportunities had a significant positive effect on Turnover Intention, indicating that absenteeism and external job opportunities were strong driving factors for turnover intention. Meanwhile, Affective Organizational Commitment and Organizational Justice did not show a significant effect. The research model was able to explain some of the variance in turnover intention, indicating that behavioral factors and labor market dynamics were more dominant in shaping employee turnover decisions. These findings provide important implications for hospital management to strengthen retention strategies through controlling absenteeism, improving perceptions of fairness, and providing more competitive career development paths.